2019
DOI: 10.1016/j.anbehav.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity increases risk perception but constrains collective behaviour during foraging by fish shoals

Abstract: Turbidity reduces the distance that animals can detect food, predators and conspecifics. How turbidity affects decision making in social contexts has rarely been investigated; moreover, it is unknown whether decreased shoaling in turbid water is due to visual constraints (a mechanistic explanation) or a reduced perception of predation risk (an adaptive explanation). Using a V-shaped decision making arena, we investigated the effect of turbidity on foraging in groups of threespined sticklebacks (Gasterosteus ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…Thus, the detection of chemical cues from the presence of prey could stimulate predators to spend more time searching for prey, but this predator behavioural change may not imply in prey capture rates at similar or higher levels than those recorded to clear waters (Johannesen et al, 2012). Furthermore, behavioural studies have demonstrated that under high turbidity prey reduce their activity (Chamberlain & Ioannou, 2019;Kimbell & Morell, 2015) and can aggregate (Johannesen, Dunn, & Morrell, 2014;Ohata, Masuda, Takahashi, & Yamashita, 2014), which could result in reduced encounters between non-visual predators and their prey and decreased prey capture rate in turbid waters. For example, Ohata et al (2011) attributed the increase in survival of larval ayu Plecoglossus altivelis co-occurring with moon jellyfish Aurelia aurita (a tactile predator) in turbid waters to a decrease in swimming activity by ayu.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the detection of chemical cues from the presence of prey could stimulate predators to spend more time searching for prey, but this predator behavioural change may not imply in prey capture rates at similar or higher levels than those recorded to clear waters (Johannesen et al, 2012). Furthermore, behavioural studies have demonstrated that under high turbidity prey reduce their activity (Chamberlain & Ioannou, 2019;Kimbell & Morell, 2015) and can aggregate (Johannesen, Dunn, & Morrell, 2014;Ohata, Masuda, Takahashi, & Yamashita, 2014), which could result in reduced encounters between non-visual predators and their prey and decreased prey capture rate in turbid waters. For example, Ohata et al (2011) attributed the increase in survival of larval ayu Plecoglossus altivelis co-occurring with moon jellyfish Aurelia aurita (a tactile predator) in turbid waters to a decrease in swimming activity by ayu.…”
Section: Methodsmentioning
confidence: 99%
“…For species of planktivorous reef fish, turbidity can cause increased attack rates but decreased attack success 33 . Other behavioural effects of turbidity include changes to anti-predator behaviour 34 38 and predation rates 39 41 , reaction distance to visual stimuli 38 , 42 – 44 , response to sensory information e.g. 45 , foraging success 33 , 38 , 46 50 , and juvenile settlement and development 6 , 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Turbid environments also influence predator-prey interactions by changing the perception of risk in fish (Gregory 1993;Chamberlain and Ioannou 2019;Ehlman et al 2019). Prey may use turbid conditions as refugia from predators, where they are less likely to be detected (Engström-Öst et al 2009).…”
Section: Introductionmentioning
confidence: 99%